Futurist Suggestions in the War Poems by Josip (Sibe) Miličić - Cabassi, Nicoletta (Poznańskie Studia Slawistyczne, 2020)
With the opening of the twentieth century, the beneficial river of the avant-gardes seemed to flood the entire European continent in a happy contamination of national cultures, giving life to an authentic supranational koine of artists: it was sometimes fusion of forms, styles, environments, cultures, a salutary effort to rejuvenate languages. The particular attention of the Italian Futurists to the new national realities was among the factors of particular attraction to the movement for South Slavs whose representative was Josip (Sibe) Miličić, who called for cultural and political renewal of his country. His direct encounter with Marinetti and Boccioni seems to leave its mark on his poetry both structurally and thematically: in the collection from 1914, Miličić reveals a new sensibility and a new rhythm: in one of his war lyrics, the futurist suggestions materialize in his first onomatopoeic attempt, suitable to undermine the lyricism of the verse by intensifying the link between the phonic aspect and the meaning. Despite their common interventionism, the Great War found the Croat and the Italian Futurists on opposite political positions concerning the Dalmatian islands and the Italian expansionism on the Adriatic. The poet’s war experience lead him to a “mature” phase starting in the twenties with his first article-manifesto. At this time he was able to reprocess his own critical identity: affirming his deeply anti-materialist and anti-industrial spiritualism, his standpoints by then had become very distant from Marinetti’s insights.